Characterization of Xanthomonas campestris Pathovars by rRNA Gene Restriction Patterns - Berthier, Yvette (1993)
Genomic DNA of 191 strains of the family Pseudomonadaceae, including 187 strains of the genus Xanthomonas, was cleaved by EcoRI endonuclease. After hybridization of Southern transfer blots with 2-acetylamino-fluorene-labelled Escherichia coli 16+23S rRNA probe, 27 different patterns were obtained. The strains are clearly distinguishable at the genus, species, and pathovar levels. The variability of the rRNA gene restriction patterns was determined for four pathovars of Xanthomonas campestris species. The 16 strains of X. campestris pv. begoniae analyzed gave only one pattern. The variability of rRNA gene restriction patterns of X. campestris pv. manihotis strains could be related to ecotypes. In contrast, the variability of patterns observed for X. campestris pv. malvacearum was not correlated with pathogenicity or with the geographical origins of the strains. The highest degree of variability of DNA fingerprints was observed within X. campestris pv. dieffenbachiae, which is pathogenic to several hosts of the Araceae family. In this case, variability was related to both host plant and pathogenicity.